Towards the engineering of molecular nanostructures: Local anchoring and functionalization of porphyrins on model-templates - Ditze, Stefanie; Röckert, Michael; Buchner, Florian; Zillner, Elisabeth; Stark, Michael Werner; Steinrück, Hans-Peter; Marbach, Hubertus (Nanotechnology, 2013)
We demonstrate that Cu(111) surfaces pre-covered with a submonolayer of copper oxide or metallic nickel are suitable model-templates for the selective adsorption and/or localized functionalization of functional molecules such as different free base porphyrins and metalloporphyrins. The oxide/Cu(111) model-template is able to steer the adsorption of tetraphenylporphyrins (TPP): 2HTPP selectively adsorbs on the bare Cu areas, and for CoTPP anchoring at the rim of the copper oxide islands is found. On the Ni/Cu(111) model-template TPP molecules are pinned on the Ni areas while they are mobile on the bare Cu surface. Interestingly, adsorption of free base octaethylporphyrin on Ni/Cu(111) leads to a local functionalization, namely the metalation to NiOEP on the Ni areas. Model-template preparation and characterization by scanning tunneling microscopy is performed at room temperature. © 2013 IOP Publishing Ltd.